Further Research the Features of the Use of Metal-Ceramic Structures in Anomalies of Development and Position of Teeth - PhD Islamova Nilufar Bustanovna; Abdulaxatov Abdug’affor Abdusattor ugli (Scientific Trends, 2024)
Anomalies of the maxilla are very common. According to various authors (1, 5), the prevalence in adults ranges from 28.8 to 37%. With regard to dental deformities, they are even more common, especially in patients with occlusal abnormalities complicated by dental defects. According to a number of studies (2), such deformities are found in 67.1 to 69.4% of patients with partial tooth loss. Various preparation methods for prosthodontics have been described in the dental literature (3, 4, 6). However, many problems remain unresolved. The purpose of this study is to identify appropriate preparation and prosthetic methods for the alveolar system in various types of abnormalities and developmental pathologies in adult patients.